Indospicine cytotoxicity and transport in human cell lines. (30th November 2018) - Sultan, Saira; Osborne, Simone A.; Addepalli, Rama; Netzel, Gabi; Netzel, Michael E.; Fletcher, Mary T.
Highlights: Hepatoxicity of the arginine-analog indospicine was tested on HepG2 cells. Intestinal toxicity of indospicine was tested on Caco-2 and HT29-MTX-E12 cells. Cytotoxicity of indospicine and 2-aminopimelic acid was higher than arginine. In vitro transport of indospicine was 2-fold higher than arginine. Abstract: Indospicine, a non-proteinogenic analogue of arginine, occurs only in Indigofera plant species and accumulates in the tissues of animals grazing on Indigofera . Canine deaths have resulted from the consumption of indospicine-contaminated meat but only limited information is available regarding indospicine toxicity in humans. In this study three human cell lines, Caco-2 (colorectal adenocarcinoma), HT29-MTX-E12 (colorectal adenocarcinoma) and HepG2 (hepatocellular carcinoma), were used to investigate the cytotoxicity of indospicine and its metabolite 2-aminopimelic acid in comparison to arginine. Indospicine and 2-aminopimelic acid were more cytotoxic than arginine, displaying the highest toxicity in HepG2 liver cells. Intestinal transport in vitro also revealed a 2-fold higher transport rate of indospicine compared to arginine. The sensitivity of HepG2 cells to indospicine is consistent with observed canine hepatotoxicity, and considering the higher in vitro transport of indospicine across an intestinal barrier, it is possible that similar ill effects could be seen in humans consuming contaminated meat.